Machine Guided Derivation of the Atlantic Meridional Overturning Circulation (AMOC) Strength - Qi‐Fan Wu; Markus Jochum; James E. Avery; Guido Vettoretti; Roman Nuterman (Geophysical Research Letters)
Abstract A machine learning based methodology is developed to determine the strength of the Atlantic Meridional Overturning Circulation (AMOC) in the Community Earth System Model (CESM). Neural networks capture relationships between various climate variables and AMOC. We then identify which of the various are the most important to control the AMOC, and then perform symbolic regression to transform complex interactions into a simple closed‐form approximation. A sensitivity analysis for this equation reveals that surface freshwater flux and potential density at 200 m depth are the main controls of the AMOC.